Review of the development of China's eco-industrial park standard system - Huang, Beijia (Animo Repository, 2019)
Eco-industrial Parks (EIP) have become a central element in China's industrial strategy to combine industrial development while minimizing environmental impacts and improving resource efficiency. National standard system has been developed as a main tool for assessing EIPs. This paper provides a review of the development of China's EIP standard system. The focus of the analysis is the new national demonstration EIP standard (HJ/T274-2015), including a review of calculation methods for some key indicators. The analysis also provides a comparison with previous standards to identify the main changes and improvements in the assessment of EIPs. Comparison findings illustrate that the new standard provides a more consistent indicator system by providing a consolidated standard system, and offering more comprehensive and quantitative indicators. Moreover, the new standard aims to better manage environmental issues by supplementing more comprehensive environmental indicators. The standard also strengthens the emphasis of the industrial symbiosis dimension in the evaluation of EIPs. By offering optional indicators and giving distinct targets based on contextual conditions for a number of indicators, the flexibility and rationality of the EIP assessments are also enhanced. Although many positive changes have been identified, there are still some shortcomings exist in the new EIP standard. The paper proposes a number of recommendations based on analyzing shortcomings, for instance further improving of the industrial symbiosis indicators, offering social benefit evaluation indicators, and strengthening the reduction action evaluation. China's experience of setting EIP standards and indicators may provide lessons for other countries’ attempts to develop industrial estate indicators. In order to observe and effectively promote industrial estates at the global range, several remaining research questions that need further exploration are put forward in this study. © 2018 Elsevier B.V.